Characterization of long-term and seasonal variations of black carbon (BC) concentrations at Neumayer, Antarctica - Weller, Rolf; Minikin, Andreas; Wagenbach, Dietmar (Atmospheric chemistry and physics. Discussions, 2013)
Abstract. Continuous black carbon (BC) observations were conducted from 1999 through 2009 by an Aethalometer (AE10) and from 2006 through 2011 by a Multi-Angle Absorption Photometer (MAAP) at Neumayer Station (NM) under stringent contamination control. Considering the respective observation period, BC concentrations measured by the MAAP were somewhat higher (median ± standard deviation: 2.1 ± 2.0 ng m−3) compared to the AE10 results (1.6 ± 2.1 ng m−3). Neither for the AE10 nor for the MAAP data set a significant long-term trend could be detected. Consistently a pronounced seasonality was observed with both instruments showing a primary annual maximum between October and November and a minimum in April with a maximum/minimum ratio of 4.5/1.6 = 3.8 and 2.7/0.64 = 4.2 for the MAAP and AE10 data, respectively. Occasionally a secondary summer maximum in January/February was visible. With the aim to assess the impact of BC on optical properties of the aerosol at NM, we evaluated the BC data along with particle scattering coefficients measured by an integrating nephelometer. We found the mean single scattering albedo of ω550 = 0.992 ± 0.0090 (median: 0.994) at a wavelength of 550 nm with a range of values from 0.95 to 1.0.
Gesehen am 15.05.2019